Family Structure, Risks, and Racial Stratification in Poverty. (1st July 2021) - Williams, Deadric T; Baker, Regina S
Abstract: Family structure remains a dominant explanation for understanding racial inequality in poverty. Yet, empirical studies show family structure does not fully account for this association. We present racial stratification as an alternative perspective emphasizing the social construction of race and how race contributes to the unequal distribution of resources. To illustrate the link between racial stratification and poverty, we rely on risk research and conceptualize risk in terms of prevalences (the percentage of people with risks) and penalties (the probability of poverty associated with risks). We assess whether family structure and risks intersect by racialized groups, and if so, whether the penalties for risks among Black and Latinx mothers, relative to white mothers, converge (i.e., smaller gap in penalties) or diverge (i.e., larger gap in penalties). Using panel data, our results revealed Black mothers had higher risk prevalence than both Latinx and white mothers. Moreover, a dramatic divergence in the penalties for risks emerged between racialized groups whereby Black and Latinx mothers experience greater disadvantage from risks than white mothers, regardless of family structure. We conclude family structure is not only an oversimplified explanation but also contributes to obscuring structural and systemic sources of racial inequality in poverty.